2017
DOI: 10.1177/1099800417701831
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Augmentation in Spontaneously Laboring, Nulliparous Women: Multilevel Assessment of Maternal BMI and Oxytocin Dose

Abstract: Background Synthetic oxytocin, the primary tool for labor augmentation, is less effective among obese women, leading to more unplanned cesarean deliveries for slow labor progress. It is not known if obese women require higher doses of oxytocin due to maternal, fetal, or labor factors related to maternal obesity. Objectives This study had two main objectives: 1) Examine the influence of maternal body mass index (BMI) on hourly doses of oxytocin from augmentation initiation until vaginal delivery in obese wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
(59 reference statements)
4
22
0
Order By: Relevance
“…21,22 It has also been shown that leptin, which has an inhibitory effect on the myometrium, is produced by adipose tissue and therefore is present in higher concentrations with increasing BMI. 9,[22][23][24] There may also be changes in the expression of function of the oxytocin receptor, as it has been shown that variants in the oxytocin receptor gene expression may lead to variable responses during labor. 16,25,26 Furthermore, an increase in oxytocin receptor expression and decrease in receptor sensitivity have been seen with increasing BMI.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 It has also been shown that leptin, which has an inhibitory effect on the myometrium, is produced by adipose tissue and therefore is present in higher concentrations with increasing BMI. 9,[22][23][24] There may also be changes in the expression of function of the oxytocin receptor, as it has been shown that variants in the oxytocin receptor gene expression may lead to variable responses during labor. 16,25,26 Furthermore, an increase in oxytocin receptor expression and decrease in receptor sensitivity have been seen with increasing BMI.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the safety and optimal use of labor interventions like oxytocin augmentation has not been established among women who are obese, although it is known that these women more often show poor response to oxytocin augementation and require higher titrations of oxytocin to achieve vaginal birth, even after spontaneous labor onset . Oxytocin use is associated with uterine tachysystole with fetal distress, and has been linked to multiple maternal and neonatal complications, prompting its classification as one of the 12 most dangerous medications used in a hospital .…”
Section: Discussionmentioning
confidence: 99%
“…After controlling for maternal, fetal, and labor characteristics, BMI alone explained 16.56% (95% Confidence Interval (CI)13.7-20.04) of the variance in hourly oxytocin doses. The authors concluded, obesity contributes to blunting of myometrial contractility and therefore a response to oxytocin [8]. This effect was seen in Hill M et al study as well.…”
Section: Resultsmentioning
confidence: 53%